Effect of contamination and purity priming on attitudes to vaccination and other health interventions: A randomised controlled experiment. Issue 45 (29th October 2021) - Bryden, Gabrielle M.; Rockloff, Matthew; Browne, Matthew; Unsworth, Carolyn
Highlights: Exposure to contamination and purity primes didn't impact ratings of vaccinations. Exposure to contamination and purity primes didn't impact ratings of alternative medicines. High levels of disgust sensitivity are related to lower ratings of vaccinations. Abstract: The objective of this experiment is to assess whether priming for contamination and purity causes a change in attitudes to health interventions, including vaccination, and complementary and alternative medicines (CAMs). An online priming experiment was conducted with four between-subject experimental conditions including photos of: 1) biological contamination, 2) chemical contamination, 3) pure environments, such as pristine landscapes, and 4) hazard signs/icons indicating physical threats. Two control conditions included photos of neutral scenes and neutral icons, whereby experimental groups were compared against the related control groups (photograph for conditions 1–3 and neutral icons for condition 4). Subjects were randomly assigned to one of the six conditions, and after exposure to the images they were asked to rate 10 conventional and alternative health interventions for effectiveness and safety, as well being assessed for disgust sensitivity using the reduced-item DPSS-R [10] . A total of 642 adults completed the experiment. Exposure to primes did not cause a differential change in ratings of health interventions. Nevertheless, higher levels of sensitivity to disgust were associated with lower ratings of the effectiveness of MMR vaccination, tetanus injection, antibiotics, and surgery; and higher levels of sensitivity to disgust were associated with higher ratings of effectiveness of vitamins/minerals. In conclusion, this online experiment did not find an experimental effect of priming for contamination and purity on subjects' ratings of the safety and effectiveness of conventional and alternative health interventions. This indicates that attitudes to these health interventions are not influenced by a temporary increase in the salience of feelings of contamination or purity. However, individual differences in disgust sensitivity are related to their attitudes to vaccination and CAM interventions.